The Role of Forensic Accounting and Investigative Auditing in Improving Fraud Detection: The Moderating Effect of Auditor Professionalism - Umniyah, Munifatul; Umaimah, Umaimah (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to analyze the effect of forensic accounting and investigative auditing on fraud disclosure, as well as to examine the role of auditor professionalism as a moderating variable. The method used is quantitative with the Partial Least Square (PLS) approach through SmartPLS software. The sample in this study consists of internal and external auditors who have experience in handling fraud. The results of this study indicate that forensic accounting and investigative auditing have a positive and significant effect on fraud disclosure. However, auditor professionalism was not found to moderate the relationship between forensic accounting and investigative auditing and fraud disclosure. These findings indicate that auditors' technical competence in forensic accounting and investigative auditing already encompasses the elements of professionalism required in the fraud detection process. This study provides practical contributions in increasing the focus on developing the technical competence of auditors and expanding theoretical studies in the field of auditing and fraud prevention.